2002
DOI: 10.1097/00000539-200210000-00029
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of Acute Tolerance to Morphine Analgesia: Concentration-Dependent or Time-Dependent?

Abstract: We evaluated the relationship of either the infusion time or the plasma morphine concentrations on the magnitude of acute tolerance to morphine analgesia in rabbits. We found that the magnitude of morphine tolerance is significantly correlated to the duration of infusion but not to the different steady-state plasma morphine concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…7,10 The benefits of OR derived from individual variability in analgesic response to opioids, in which various factors such as age, gender, type of cancer, changes in renal or hepatic function, or emotional status can all play a role. 11 Numerous factors, including pharmacodynamic variability, genetic variability, 12,13 neuronal changes in response to chronic opioid exposure, [14][15][16] the specific N-methyl-d-aspartate receptor activity of some opioids, 17,18 and the phenomenon of receptor blockade 19 may be involved in this mechanism. Variability in pharmacodynamic parameters includes differences in bioavailability, pharmacological interactions, different metabolism routes, and different production of active metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…7,10 The benefits of OR derived from individual variability in analgesic response to opioids, in which various factors such as age, gender, type of cancer, changes in renal or hepatic function, or emotional status can all play a role. 11 Numerous factors, including pharmacodynamic variability, genetic variability, 12,13 neuronal changes in response to chronic opioid exposure, [14][15][16] the specific N-methyl-d-aspartate receptor activity of some opioids, 17,18 and the phenomenon of receptor blockade 19 may be involved in this mechanism. Variability in pharmacodynamic parameters includes differences in bioavailability, pharmacological interactions, different metabolism routes, and different production of active metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…The development of acute tolerance to the analgesic effect of morphine is well evidenced in animal [1,[12][13][14][15] and human studies [2,16,17], although there are some controversial results [18,19]. Our previous experiment and most clinical work [3] focused on large preoperative or intraoperative doses of opioid administration.…”
Section: Discussionmentioning
confidence: 99%
“…An audit of large numbers of patients has shown the increased risks of respiratory depression [21,22]. The variations between different studies might be due to their relatively small sample size for detecting small differences, different background infusion rates or agents, different types of surgery that induce various degrees of pain [12], too-short duration of PCA use to establish acute tolerance, or failure to evaluate pain intensity at rest. Two articles produced by Doyle et al even found that, in children aged between 6 and 12 years undergoing an appendectomy, the inclusion of a background infusion of 4 μg/kg/hr morphine in a PCA regimen did not increase morphine usage or frequency of side effects, but was associated with less hypoxemia and a better sleep pattern than with no background infusion [4].…”
Section: Discussionmentioning
confidence: 99%
“…У той же час у пацієнтів, які отримували низькі дози реміфентанілу і 20 мг Нефопаму в/в за 30 хвилин до закінчення операції, гостра толерантність до опіоїдів взагалі не розвивалась [13]. оригинальные исследования / Original Researches В іншому дослідженні була виявлена чітка кореляція тривалості інфузії опіоїдних аналгетиків і вираженості толерантності до морфіну [8]. Стимуляція мю-опіоїдних рецепторів є тригером активації NMDA-рецепторів, які, у свою чергу, запускають механізм формування центральної сенситизації (вторинної гіпералгезії).…”
Section: обґрунтування застосування нефопаму для знеболювання та резуunclassified